TEACHER STRATEGIES OF ISLAMIC RELIGIOUS EDUCATION IN OVERCOMING NEGATIVE VERBALISM BEHAVIOR AMONG SEVENTH-GRADE STUDENTS - Maliq Rahman Syam; Indah Nurul Hazairin (Academic Bright Collaboration, 2026)
This study aims to analyze the strategies implemented by Islamic Religious Education (PAI) teachers in overcoming negative verbalism behavior among seventh-grade students at SMP Negeri 40 Satu Atap Kerinci. This study employed a qualitative field research design. Data were collected through non-participant observations, semi-structured interviews, and documentation involving PAI teachers, students, homeroom teachers, and the school principal. Participants were selected purposively based on their involvement in students’ character development and communication behavior. Data were analyzed using the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing. Triangulation and member checking were applied to ensure data trustworthiness. The findings revealed that negative verbalism among students appeared in the form of harsh language, mockery, verbal humiliation, high-tone communication, and provocative speech. The study identified peer influence, social media exposure, family communication patterns, and low awareness of communication ethics as major inhibiting factors, while teacher modeling, religious school culture, and habituation programs served as supporting factors. PAI teachers addressed these behaviors through integrated strategies involving modeling (uswah hasanah), habituation, moral advice, educational sanctions, and collaboration with parents. These strategies gradually contributed to improving students’ language politeness and emotional awareness. The study was limited to one junior high school context and focused on qualitative exploration. This study highlights the integration of preventive and corrective Islamic educational strategies in addressing negative verbalism behavior among adolescents.